Dynamics and forecast of morbidity and mortality from prostate cancer in St. Petersburg - N. G. Petrova; K. Yu. Krotov; D. B. Vcherashniy (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
The paper presents the characteristics of primary disease incidence, prevalence and mortality from prostate cancer among men's population of St. Petersburg (normal and age-standardized rates); analyzed their dynamics for 20 years; shows the calculated trend of these indicators up to 2020.